2000
DOI: 10.1093/deafed/5.3.266
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sign Language on the Cognitive Development of Deaf Children: The Case of Theories of Mind

Abstract: The ability to attribute false beliefs (i.e., demonstrate theory of mind) by 155 deaf children between 5 and 8 years of age was compared to that of 39 hearing children ages 4 to 6. The hypotheses under investigation were (1) that linguistic features of sign language could promote the development of theories of mind and (2) that early exposure to language would allow an easier access to these theories. Deaf children were grouped according to their communication mode and the hearing status of their parents. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
6
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 20 publications
5
104
6
13
Order By: Relevance
“…Con respecto a la utilización de IC, sólo encontramos diferencias significativas en la tarea de Alternancias Motoras (F(1,25) = 4.7; p < 0.04), obteniendo una puntuación significativamente más alta los niños con IC. Campbell, MacSweeney y Waters, 2007;Courtin, 2000;Emmorey et al, 2002). Sin embargo, es preciso señalar que la gran mayoría de los niños signantes que participaron en el presente estudio, no eran hijos de padres sordos, por lo que no adquieren la LSE de forma natural y la mayoría de ellos tampoco fueron introducidos de forma temprana a este modo de comunicación.…”
Section: Resultsunclassified
“…Con respecto a la utilización de IC, sólo encontramos diferencias significativas en la tarea de Alternancias Motoras (F(1,25) = 4.7; p < 0.04), obteniendo una puntuación significativamente más alta los niños con IC. Campbell, MacSweeney y Waters, 2007;Courtin, 2000;Emmorey et al, 2002). Sin embargo, es preciso señalar que la gran mayoría de los niños signantes que participaron en el presente estudio, no eran hijos de padres sordos, por lo que no adquieren la LSE de forma natural y la mayoría de ellos tampoco fueron introducidos de forma temprana a este modo de comunicación.…”
Section: Resultsunclassified
“…The first of these showed that there was no effect of severity of hearing loss on error rate, (F (1,23) = .10, p = .75). As research has shown that deaf children with signing family members perform as well as age and intelligence matched hearing children on emotion recognition and theory of mind tasks (Courtin, 2000;Peterson & Siegal, 1999); we compared the total numbers of correct scores, obtained by the twelve deaf children who had signing family members (aged 6 years 9 months-15 years 8 months: mean = 10 years 3 months, SD = 3.4) with those obtained by the twelve children without signing family members (aged 6 years 8 months-16 years 10 months: mean = 12 years 4 months, SD = 2.4). This included 7 families where only the mother signed and 4 where both parents signed.…”
Section: Degree Of Hearing Loss and Signing Abilitymentioning
confidence: 99%
“…There is general consensus that though their grammatical structures are different from those of spoken language, they can be analyzed using the frameworks of phonological, morphological and syntax techniques derived from spoken language studies (Baker & Cokely, 1980;Stokoe, 1980). With recent advances in sign linguistics, many studies have been conducted in developmental psychology and cognitive psychology on the process of sign language acquisition in deaf children (e.g., Newport, E. L. 1990;Courtin, 2000;Senghas, Kita, & Ozyurek, 2004).…”
Section: )mentioning
confidence: 99%